A morphometric and chemosystematic study on the Abies Miller (Fir) species in Turkey - Bagci, E; Babaç, MT (Soc Botanique France, 2003)
Naturally distributed Abies (Fir) Miller taxa comprise five subspecies belonging to two species (A. nordmanniana subsp. nordmanniana, A. n. subsp. bornmuelleriana, A. n. subsp. equi-trojani, A. cilicica subsp. cilicica, A. c. subsp. isaurica) in Turkey. A multi-level study of the genus Abies is presented. Infrageneric states and chemosystematic relationships are discussed by using some selected essential oil components and morphometrical characters. Morphologic and morphometric analysis are carried out on 20 Abies population and essential oil analysis on the twig with needle are carried out by using GC. techniques. The qualitative major constituents are found as same in the whole studied species but their quantitative content varies significantly. Inter and intrapopulational variations are found at the high ratio in the Abies taxa. The results are presented in graphical form, allowing patterns of variable intercorrelations and compared with phylogenetic patterns. Tree to tree variation of quantitative terpene composition of the leaf oil is sufficiently to permit chemosystematic discussions and understanding evolutionary phenomenon in the light of literatures.
Keywords: Abies L.; Pinaceae; fir; essential oil; chemosysternatics; phylogenetics